Architectural design quality indicators for residential buildings in Lattakia - Ramzi Alshaikh; Mohammed Mannon; Ranim Khoder (Tishreen University, 2017)
تعتبر عملية التصميم المعماري معقدة نسبياً نظراً لاختلاف مضمونها مع اختلاف المستخدمين, بالتالي فإن كل عملية تصميم لها ميزاتها الخاصة التي يصعب توحيدها, كما ينظر البعض إلى التصميم المعماري أنه عبارة عن عملية إنتاج لمرة واحدة, مما يجعل من الصعوبة قياس جودة التصميم المعماري نتيجة لعدم نمطية المعايير المستخدمة. البحث تناول عملية التصميم المعماري على أنها نتيجة لمجموعة من القرارات حول عدة مؤشرات تشكل عناصر الجودة في التصميم ,التي يجب العمل عليها لتحسين الجودة في أي تصميم . يقدم البحث دراسة وصفية حول أدوات تقييم جودة التصميم المعماري المستخدمة عالمياً (على سبيل المثال DQI، DEEP، AEDET، HQI، LEED، BREEAM) لمعرفة معايير الجودة المعتمدة في كل أداة كخطوة نحو تشكيل إطار عام لمفهوم جودة التصميم المعماري للمباني السكنية, من خلال إجراء دراسة ميدانية للمعايير المستخلصة لتحديد درجة أهمية معايير جودة التصميم المعماري بالنسبة للمباني السكنية في مدينة اللاذقية. خلص البحث إلى مجموعة من المعايير الناظمة لجودة التصميم المعماري للمباني السكنية في مدينة اللاذقية. Architectural design process is relatively complex considered due to the different content with users difference, therefore, each design has its own advantages that are difficult to standardize the process, as some have seen as architectural design that is a process of producing a one-time, making it difficult architectural design quality measurement result of not atypical The criteria used. Architectural design will be addressed as a result of a series of decisions on the key aspects that make up the elements of quality in design and that it must work to improve the quality of any design process. The research presents a theoretical study on the global architectural design used for quality assessment tools (eg DQI, DEEP, AEDET, HQI, LEED, BREEAM, BQA) to see the certified quality standards in each tool as a step towards the formation of a general framework for the concept of the architectural design of residential buildings quality of during a field study of the standards derived to determine the architectural design standards for residential buildings in Latakia The research found a set of standards governing the quality of the architectural design of residential buildings in Lattakia.